Letter : Spanish Children. Evacuees - Southport Trades Council and Labour Party ; Derby and District Trades Council; Amatt, J. S.
1939-10 038-0071-002 DERBY AND DISTRICT TRADES COUNCIL 89, Ashbourne Rd. DERBY Date as Postmark. To Secretary's of Trades Councils. Dear Sir, Madam. SPANISH CHILDREN, EVACUEES. refer to TUC I have to inform you that the above Council, having considered the evacuation of children from danger Zones for which the Government is mainly responsible for their maintainence, have decided to write the Home Secretary urging that the few remaining Spanish Children remaining in this Country should be treated and provided for in the same way as the English evacuees. The Derby Trades Council would greatly appreciate your Councils support in this matter by writing the Home Secretary in similar terms. The need is urgent as the Spanish Children are being solely supported by working class efforts. Yours faithfully, J.S. Amatt SECRETARY. 292/946/38/71(II)